Processus d'institutionnalisation et éducation : l'enseignant médiateur des transformations de l'élève - Loïc Clavier
The theory of situations (contract, devolution, institutionalization) allows pupils to access a decontextualized knowledge, but has an irreducible dimension of heteronomy linked to control rather than to evaluation. The use of Ardoino's work on evaluation in the sociological framework of Castoriadis makes it possible to revise the concepts of the theory of situations in the sense of the autonomy of the pupil. The teacher can become a mediator of the student's transformations (agent, actor, author) by replacing the control with the evaluation, as an accompaniment to the learning and unveiling of the imaginary of the class (explicitation of the didactic contract). In the same way, problematization as a process of permanent self-questioning constitutes the evaluation and the self-reflection of the student on himself allows to reconfigure the theory of situations in a sense of autonomy.